ASAS-ASAS PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM MULTIKULTURAL - Abdul Halim (Universitas Islam Lamongan, 2017)
Basically education is an instrument for humans use to advance their civilization and culture. education is always running and developing in line with human life. Islamic education as an education actvity which is colored by the spirit and values of Islam will also develop during the life of members of islam comunity. Changes and developments in Islamic education seem so fast, whereas the life of today's society as if we live without division and distance as the impact of globalization. it gives the impression that the cultural differences of one society with others will be apparent. The apparent differences will be a time bomb that will explode in time, further leads to disharmony in society or cultural clashes. In the meantime Islamic education must be able to enter space building an educational model that develops multicultural values such as tolerance, fair education and education that uphold the value of equality. Therefore, to develop this educational model needs to touch the curriculum as the heart of education. as we know that in developing the curriculum requires principles such as theological, philosophical, juridical and sociological principles in order to the development is not uprooted from the basic values of Islamic educationKeywords: Principles, Curriculum, Multicultural Islamic Education